Development of a novel predictive model for a successful stone removal after flexible ureteroscopic lithotripsy based on ipsilateral renal function: a single-centre, retrospective cohort study in China - Hong Li; Liang Zhou; Xi Jin; Yucheng Ma; Zhongyu Jian; Liyuan Xiang; Deyi Luo; Kun-Jie Wang (BMJ Open)
Objectives The aims of this study were to investigate the effect of preoperative ipsilateral renal function on the success of kidney stone removal with flexible ureteroscopic lithotripsy and to develop a predictive model based on the results.Design Retrospective cohort study.Setting Data from the 2001–2012 period were collected from the electronic records of West China Hospital, Sichuan University.Participants 576 patients who underwent flexible ureteroscopic lithotripsy were included in the study.Primary outcome Stone-free rate (SFR) after the procedures.Results In patients with suspected impaired kidney function, the overall SFR was 70.1%. Stone volume (OR 1.46; 95% CI 1.18 to 1.80), lower calyx stones (OR 1.80; 95% CI 1.22 to 2.65), age (OR 1.02; 95% CI 1.00 to 1.04), body mass index (OR 1.10; 95% CI 1.04 to 1.17) and estimated glomerular filtration rate of the affected kidney (OR 0.95; 95% CI 0.94 to 0.97) were identified as independent predictors of SFR. Lasso regression selected the same five predictors as those identified by univariate and multivariate logistic regression analyses, thus verifying our model. The mean area under the curve, based on 1000 iterations and 10-fold validation, was 0.715 (95% CI 0.714 to 0.716). The Hodges-Lehmann test and calibration curve analysis revealed no significant mismatch between the prediction model and the retrospective cohort.Conclusion Ipsilateral renal function may be a novel independent risk factor for kidney stone removal with flexible ureteroscopic lithotripsy. A novel nomogram for predicting SFR that uses stone volume, lower calyx stones, age, body mass index and estimated glomerular filtration rate was developed, but remains to be externally validated.